Improving Naming Abilities Among Healthy Young-Old Adults Using Transcranial Direct Current Stimulation - Lifshitz-Ben-Basat, Adi; Mashal, Nira (Journal of psycholinguistic research, 2018)
Transcranial direct current stimulation (tDCS) is a noninvasive tool to facilitate brain plasticity and enhance language abilities. Our study aims to search for a potential beneficial influence of tDCS on a cognitive linguistic task of naming which found to decline during aging. A group of fifteen healthy old adults ( M = 64.93 ± 5.09 years ) were tested in naming 50 pictures of objects. Each subject participated in two sessions spanning on a one week period. One session included active tDCS stimulation and the other sham-placebo like stimulation. Subjects were blinded to stimulation type. During the active stimulation a bilateral protocol of anodal tDCS to the left Inferior Frontal Gyrus (IFG) combined with cathodal tDCS to the right IFG was delivered. Half of participants received active stimulation at the first session and sham at the second and half received the stimulations at the opposite order. Naming reaction time was measured at baseline, after active tDCS stimulation and after sham. 10 min of bilateral tDCS stimulation which was given after sham (training) was found to reduce naming reaction time among healthy adult subjects. These findings support the cooperative model (Weems and Reggia in Brain Lang 89:554–568, 2004 ) and point on strong interhemispheric connections during naming processing. It is also demonstrate the advantage of training to intensify the therapeutic effect of tDCS. Our results pinpoint on a potential tool to facilitate naming among aging people.